It is about how the properties are used.

Asked by  | 2nd Jul, 2013, 09:43: AM

Expert Answer:

Please ask one question at a time. The answer to your first question is as follows:
 
tan-1 (cosx /1-sinx)
= tan-1 ( { cos2 (x/2) - sin (x/2) } / [cos(x/2) - sin(x/2) ]2 )
= tan-1 ( { cos(x/2) + sin(x/2) } [cos(x/2) - sin(x/2) ] )
Divide the Numerator and Denominator by cos(x/2)
= tan-1( { 1 + tan(x/2) } / [ 1- tan(x/2) ] )
= tan-1( { tan?/4 + tan(x/2) } / [ 1-tan?/4 tan(x/2) ] )
= tan -1 ( tan( ?/4 + (x/2) ) )
= ?/4 + (x/2)

Answered by  | 6th Jul, 2013, 11:39: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.